Gender Diversity on Boards: A Myth or a Missed Opportunity for Financial Performance? - Daniel Amo; María-José García-López; Hamid Hamoudi (Administrative Sciences)
This study examines the influence of gender composition on corporate financial performance, measured by the Price-to-Earnings (P/E) ratio and Tobin’s Q, considering both male and female directors. Using an econometric panel data analysis, a dual fixed effects model and the Generalized Method of Moments (GMM) were applied to all Spanish listed companies from 2017 to 2022. The findings reveal no statistically significant correlation between gender diversity in the boards of directors (hereinafter, the board) and the financial performance indicators analyzed. However, a significant association was observed between gender diversity in non-board managerial positions and improved firm economic performance. This challenges the traditional focus on female representation in boards by highlighting the broader impact of gender composition across corporate structures. This study underscores the need for a comprehensive theoretical framework that considers both male and female directors to better understand gender diversity dynamics in governance. From a practical perspective, the results emphasize the importance of promoting gender diversity not only at the board level but also across all managerial positions. Policymakers and corporations should implement strategies to foster balanced gender representation throughout management levels to enhance economic performance.